Taxonomy and Phylogeny of Two Tintinnid Ciliates of Leprotintinnus (Protista, Ciliophora, Choreotrichida) Combining the Loricae, Cytological, Ontogenetic Features, and Barcoding Genes - Hu, Tao; Wang, Zhaoyi; Liu, Weiwei; Lin, Xiaofeng (Frontiers in Marine Science, 2022)
Tintinnid ciliates are a highly diverse and essential group in the marine planktonic microbial loop. However, most of the known tintinnids were recorded only by the lorica characters and very few of them had been studied on their cytological features. In this study, the morphological characters of the lorica, ciliary pattern, nuclear apparatus, ontogenesis, and the molecular phylogeny of two poorly known tintinnid ciliates, Leprotintinnus nordqvisti (Brandt, 1906) Kofoid and Campbell (1929) and L. simplexSchmidt (1902), isolated from coastal waters of southern China, were investigated based on living observation, silver staining, three nuclear ribosomal DNA markers (18S, ITS1-5.8S-ITS2, and 28S genes) and one mitochondrial DNA marker (CO1 gene). For the first time, the somatic ciliary pattern of the genus Leprotintinnus was disclosed, viz., comprising a ventral, a dorsal, and a posterior kinety as well as a right, a left, and a lateral ciliary field. The diagnoses of both Leprotintinnus species were improved and the neotype was assigned. The ontogenesis of L. nordqvisti was in enantiotropic division mode with the new dorsal and posterior kineties generated de novo. The molecular phylogeny confirmed that Leprotintinnus species are closely related to some species of Tintinnopsis, Stylicauda, Rhizodomus, and Climacocylis. The anterior extending of the ventral kinety together with some of the lateral kinety is likely to be a distinguishing feature to determine their systematic relationships. This study also revealed that (i) the lorica of L. nordqvisti is polymorphic or plastic; (ii) Leprotintinnus tubulosusRoxas (1941) might be a synonym of L. nordqvisti; (iii) Leprotintinnus neriticus sensu Yoo et al. (1988) might be a misidentification of L. simplex.